Was heisst und zu welchem Ende studiert man romanische Literaturwissenschaft? Potsdamer Vorlesungen zur Romanistik - Ette, Ottmar (AULA, 2022)
This Potsdam lecture attempts to more closely define the object of "Romance literary studies" within the context of the literatures of the world, to define the exceptional, even essential significance of this object of study, and to prospectively inquire into future opportunities for research, study, and life in the field of Romance literary studies.